2007
DOI: 10.1111/j.1570-7458.2006.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological adaptation in host races of Tephritis conura

Abstract: The present study investigates morphological differentiation among host races of the fruit fly Tephritis conura Loew (Diptera: Tephritidae) for two fitness‐related traits and whether these traits are host induced or genetically determined. Flies were analyzed from independent sympatric regions, and from one syntopic site where parental host plants [Cirsium heterophyllum (L.) Hill. and Cirsium oleraceum (L.) Scop. (Cardueae)] and hybrid plants (C. heterophyllum×C. oleraceum) co‐occur. As both host races may ovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 62 publications
3
35
3
Order By: Relevance
“…Genetic analyses have shown that gene flow among T. conura infesting C. heterophyllum or C. oleraceum is severely restricted (Seitz and Komma 1984; Diegisser et al 2006a,b) and that host-specific morphological adaptations exist (Diegisser et al 2007). In hostchoice experiments, T. conura significantly preferred to fly to and to stay on the host-plant species from which they had emerged (Komma 1990; Diegisser 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analyses have shown that gene flow among T. conura infesting C. heterophyllum or C. oleraceum is severely restricted (Seitz and Komma 1984; Diegisser et al 2006a,b) and that host-specific morphological adaptations exist (Diegisser et al 2007). In hostchoice experiments, T. conura significantly preferred to fly to and to stay on the host-plant species from which they had emerged (Komma 1990; Diegisser 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the evolution of the ovipositor (egg-laying structure) is critical for a female insect's reproductive fitness. Examination of ovipositor morphology within insect lineages confirms that ovipositor morphology is under selection and responds evolutionarily to changes in host plant use (Price and Carr 2000;Jousselin et al 2006;Diegisser et al 2007;Joy and Crespi 2007;Leschen and Buckley 2007;Urban and Cryan 2007). For many insect groups, copulation must also occur through the same opening as egg deposition.…”
mentioning
confidence: 99%
“…Cirsium palustre has significantly smaller flower heads than C. heterophyllum (Hegi 1979). Consequently, flies exploiting both C. palustre and C. heterophyllum (British flies) are expected to evolve shorter oviscapes than flies exploiting only C. heterophyllum (continental flies) (Diegisser et al 2007). British T. conura have adapted the ovipositor length to exploit the more common C. palustre but this has not resulted in a detectable host-related genetic shift under the current ecological conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Potential factors restricting diet breath include natural enemies (Menken et al 1992), interspecific competition (Denno et al 1995), physiological constraints (Rosenthal and Berenbaum 1992) or the need to adapt to the host's morphology (Diegisser et al 2007) or phenology (Feder et al 1993;Dambroski and Feder 2007). The most proximate cause determining an insect's host range, however, is its behaviour (Bernays and Chapman 1994;Gassmann et al 2006); whether or not a host plant is utilised as oviposition substrate depends on the female's host choice.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation